Reduction of hip joint reaction force via medio‐lateral foot center of pressure manipulation in bilateral hip osteoarthritis patients. Issue 10 (29th February 2016) - Solomonow‐Avnon, Deborah; Haim, Amir; Levin, Daniel; Elboim‐Gabyzon, Michal; Rozen, Nimrod; Peled, Eli; Wolf, Alon
ABSTRACT: Loading/excessive loading of the hip joint has been linked to onset and progression of hip osteoarthritis. Footwear‐generated biomechanical manipulation in the frontal plane has been previously shown in a cohort of healthy subjects to cause a specific gait adaption when the foot center of pressure trajectory was shifted medially, which thereby significantly reduced hip joint reaction force. The objective of the present study was to validate these results in a cohort of female bilateral hip osteoarthritis patients. Sixteen patients underwent gait analysis while using a footworn biomechanical device, allowing controlled foot center of pressure manipulation, in three para‐sagittal configurations: medial, lateral, and neutral. Hip osteoarthritis patients exhibited similar results to those observed in healthy subjects in that a medial center of pressure led to an increase in inter‐maleolar distance while step width (i.e., distance between right and left foot center of pressure) remained constant. This adaptation, which we speculate subjects adopt to maintain base of support, was associated with significantly greater hip abduction, significantly decreased hip adduction moment, and significantly reduced joint reaction force compared to the neutral and lateral configurations. Recommendations for treatment of hip osteoarthritis emphasize reduction of loads on the pathological joint(s) during daily activities and especially in gait. Our results show that a medially deviated center of pressure causes a reduction in hip joint reaction force. The present study does not prove, but rather suggests, clinical significance, and further investigation is required to assess clinical implications. © 2016 Orthopaedic Research Society. Published by Wiley Periodicals, Inc. J Orthop Res 34:1762–1771, 2016.